Todesursachen bei amyotropher Lateralsklerose: Ergebnisse aus dem ALS-Register Rheinland-Pfalz = Causes of death in amyotrophic lateral sclerosis : results from the Rhineland-Palatinate ALS registry - Wolf, Joachim; Safer, Anton; Wöhrle, Johannes C.; Palm, Frederick; Nix, Wilfred A.; Maschke, Matthias; Grau, Armin J. (Der Nervenarzt, 2017)
Background: Amyotrophic lateral sclerosis (ALS) is associated with an increased mortality. Knowledge of possible causes of death could lead to an individualization of the palliative treatment concept and result in a differentiated palliative treatment pathway. Currently, only few systematic data are available on the heterogeneity of causes of death associated with ALS. Objective: Analysis of the various causes of death in a prospective population-based German cohort of ALS patients. Material and methods: Analysis of data of the Rhineland-Palatinate ALS registry in which newly diagnosed patients who had been identified between October 2009 and September 2012 were prospectively enrolled and followed up at regular intervals. From this prospective cohort study the causes of death were elicited based on information provided by the attending physicians, family members and by means of death certificates registered by the regional health authorities in Rhineland-Palatinate. Results: Out of 200 ALS patients registered 148 died between register initiation on 1 October 2009 and the end of follow-up on 30 September 2015 (78 males and 70 females, death rate 74%). The most frequent cause of death was respiratory failure as a consequence of weakness of respiratory muscles (n = 91, 61%). Less frequent causes of death were pneumonia (n = 13, 9%), terminal cachexia (n = 9, 6%) and death from cardiovascular causes including sudden death (n = 9, 6%). Cases of suicide were rare (n = 3, 2%) as were deaths due to concurrent diseases (n = 2). In 21 cases (14%) the exact cause of death could not be clarified. Differences in the causes of death only showed a tendency towards the ALS phenotype. Respiratory failure was the cause of death in all patients with a respiratory phenotype and in 78% of patients with flail arm syndrome. Despite the low number of patients (8%) with additional frontotemporal dementia (FTD) a distinct difference in causes of death between those with and without FTD could be observed. Death due to respiratory failure was less frequent in ALS patients with FTD (33% vs. 65%) while pneumonia was more frequent (27% vs. 7%). Conclusion: Respiratory failure was the most frequent cause of death in our cohort of ALS patients. In contrast, pneumonia and nutritional disorders played a less important role as the cause of death. The phenotypic expression of ALS might in part allow the cause of the prospective death to be predicted. Differentiation of ALS phenotypes is an important foundation for patient counseling on the process of dying to be expected and for the determination of an individual palliative concept.